Inequalities in smoking and obesity in Europe predicted to 2050: Findings from the EConDA project. Issue 5 (July 2018) - Pérez-Ferrer, Carolina; Jaccard, Abbygail; Knuchel-Takano, Andre; Retat, Lise; Brown, Martin; Kriaucioniene, Vilma; Webber, Laura
Aims: The aim of this study was to project educational inequalities in obesity and smoking prevalence to 2050 based on past obesity and smoking trends by education level. Methods: Data on obesity (body mass index ≥ 30) and smoking prevalence (current smokers) by education level (tertiary education and less than tertiary) from nationally representative cross-sectional surveys were collected for the following six countries participating in the Economics of Chronic Diseases project (EConDA): England, Finland, Lithuania, the Netherlands, Poland (obesity only) and Portugal (obesity only). A nonlinear multivariate regression model was fitted to the data to create longitudinal projections to 2050. Inequalities were measured with a prevalence ratio and a prevalence difference using projected obesity/smoking prevalence. Results: Educational inequalities in obesity prevalence are projected to increase in Finland, Lithuania and England for men, and in Lithuania and Poland for women, by 2050. Obesity prevalence is projected to increase faster among the more advantaged groups in England, Portugal, Finland and the Netherlands among women, and Portugal and the Netherlands among men, narrowing inequalities. In contrast to obesity, smoking prevalence is projected to continue declining in most of the countries studied. The decline is projected to be faster in relative terms among more advantaged groups; therefore, relative educational inequalities in smoking prevalence are projected to increase in all countries. Conclusions: Widening educational inequalities in obesity and smoking prevalence are expected in several European countries if current trends in obesity and smoking prevalence are unaltered. This will impact on inequalities in morbidity and mortality of associated diseases such as diabetes, coronary heart disease and chronic obstructive pulmonary disease.